Un atlas-web pour comparer l’exposition individuelle aux pollutions atmosphérique et sonore selon le mode de transport - Philippe Apparicio; Jérémy Gelb; Marie-Ève Mathieu (Cybergeo, 2019)
The individual and collective benefits of bicycling in urban environments are well known nowadays. On the individual level, cycling helps to improve people’s physical and mental health, and, collectively, it reduces healthcare costs, traffic congestion, as well as air and noise pollution.Several studies have recently compared the levels of exposure to air pollutants and noise according to the mode of transportation used (car, bicycle, or public transit) in a number of cities around the world. As far as we know, the results of these studies have never been disseminated in the form of a web-mapping application. This would however be a good way to encourage the transfer of knowledge to urban planners and the general public.The aim of this article is therefore to suggest a methodology based on free software and libraries for deploying an interactive web atlas comparing individual exposure to air and noise pollutants in Montreal according to the mode of transportation used. To this end, the structuring of the primary data, the architecture, and the functionalities of the atlas are all extensively discussed.